The Little Book That Lost Its Author. - Caron, Amber (Boulevard)
The article discusses the incidence of "The Great Automatic Grammatizator" short story of author Roald Dahl becoming a realty with the invention of the "Novel Writer" story-generating computer software by computer scientist Sheldon Klein in 1973. It describes the creation of the first academic program in cognitive science by cognitive science professor at University of Sussex, Margaret Boden. It also stresses on the relationship between deep reading and good writing.